The possible pathogenesis of cemento-osseous dysplasia: A case series and discussion - Ömer Günhan; Devrim Kahraman; Ülker Karagece Yalçın (Elsevier, 2021)
Cemento-osseous dysplasias (COD) are peculiar jawbone lesions. They arise in the tooth-bearing areas, mostly in the mandibles of women, and have no known occurrence in the other bones. Neural crest-derived periodontal fibroblasts may form disorganized cemento-osseous structures that have been observed to be radiologically sclerotic.We performed a retrospective immunohistochemical study on the tissues of 16 patients diagnosed with COD using biopsy. Some patients displayed a history of bruxism and jaw clenching. The selection of beta-catenin, cyclin D1, nestin, estrogen receptor, tubulin, and integrin antibodies was based on factors that may be pathogenetically significant.COD develops as a consequence of the jawbone-specific cemento-osseous reparative process that far from remodelization. Parafunctional mechanical effects are assumed to form these lesions.